Nutrient balance in the soil and nutritive characteristics of maize silage cut at different heights - Hülse, Julio; Neumann, Mikael; Ueno, Robson Kyoshi; Heker, Julio Cezar; Figueira, Danúbia Nogueira [UNESP]; Sandini, Itacir Eloi; Müller, Marcelo Marques Lopes; Horst, Egon Henrique; Vigne, Gabriela Letícia Delai (Universidade Estadual de Londrina, 2017)
Maize harvesting for silage promotes intense use of soil nutrients. The increase in forage harvesting time can ease nutrient use and benefit the nutritional quality of the silage. However, this practice may be economically unviable due to the reduction in the volume of harvested forage. The objective of our experiment was to evaluate several agronomic parameters, such as production, plant composition, nutritional value of silage and nutrient balance in the soil by harvesting the maize plant at different silage heights: 0.20; 0.40; 0.60; 0.80 and 1.00 m above the ground. The experimental design was completely randomized, with five treatments with five repetitions. Representative plants in each plot were cut and fragmented in a forage machine. This material was homogenized and ensiled in experimental polyvinyl chloride (PVC) silos. Each 0.10 m increase at harvest provided an increase of 0.65% in the dry matter content of the forage and reduced harvest to 339 kg ha-1 of dry matter. The presence of grains in the forage increased linearly 1.24% for every 0.10 m at the time of harvest. The levels of neutral detergent fiber, acid detergent fiber and silage lignin had a linear decrease of 4.5, 2.8 and 9.6%, respectively, per each 0.10 m lift crop height. Regarding the total digestible nutrients, dry matter intake and the relative forage, these values had a linear increase of 0.5, 7.2 and 8.2%, respectively. For each 0.10 m increase in cutting height, there was a decrease in soil nutrients, namely 3.6 kg ha-1 N, 1.3 kg ha-1 P2O5, 9.5 kg ha-1 K2O, 0.9 kg ha-1 CaO and 1.2 kg ha-1 MgO. Even with the harvest at 1.00 m above the ground, nutrient recycling nutrients by necromass is not sufficient to balance the potassium balance in the soil, causing a decline of 37.69 kg ha-1 K2O. The maize harvest to 0.47 m height represented the best relationship between silage quantity and quality, being the height that presents the greatest potential for economic return, and can fund management practices and soil fertilization to prevent degradation in foraging systems, mainly to overcome the negative balance of potassium in the system.
Keywords: Harvest time; Nutrient use; Potassium; Silage quality